[Ru(N∧N∧N)2-Ce]-based framework for photocatalytic sulfide oxidation and hydrogen production. Issue 17 (22nd April 2022) - Yu, Yong-Hui; Huang, Sheng-Li; Yang, Guo-Yu
Abstract : The visible-light-responsive Ru(N ∧ N ∧ N)2 -unit endows Ce frameworks with photocatalytic activities for sulfide oxidation and hydrogen production. Abstract : Using the photosensitized Ru(N ∧ N ∧ N)2 -metalloligand, a series of Ce frameworks were synthesized. The incorporation of the visible-light-responsive Ru(N ∧ N ∧ N)2 -unit endows the Ce frameworks with photocatalytic activities in both sulfide oxidation and hydrogen production. The doping of Zr and particularly the oxidation state of Ce has great influence on the photocatalytic properties of the Ce frameworks.